Risk sharing and firm size: Theory and international evidence - Mariassunta Giannetti (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
This paper investigates the relationship between financial development and firm size. The model shows that the efficiency of the financial system, measured by the level of monitoring costs, affects the extent of risk sharing within an economy and through this channel the availability of external finance to growing firms. If the provision of finance to projects is concentrated in few individuals and firm shocks are idiosyncratic, the risk premium is likely to rise with the amount of funds firms demand. As a consequence, keeping constant the level of opacity and risk, firms with better growth opportunities face higher costs of external finance in countries where the financial system does not favor risk sharing; this limits firm size. Empirical evidence is also provided. Financial constraints appear more stringent for firms whose optimal size is larger in countries where the financial system is less developed.
Keywords: G30; O16; 330; risk sharing; firm size; financial constraints; financial development; Betriebsgröße; Investitionsrisiko; Theorie; Investitionsrecht